Why Does Happiness Respond Differently to an Increase vs. Decrease in Income? - Richard A. Easterlin (Institute of Labor Economics (IZA), 2021)
The answer is that people's evaluations of their income situation are based on different considerations when the economy is expanding and when it is contracting. When, in the course of economic growth, incomes generally are rising, evaluations tend to be dominated by "social comparison"—what is happening to the incomes of others. An increase in the incomes of others undercuts the tendency for happiness to grow with an increase in one's own income, and happiness remains fairly constant. But in a recession, as people increasingly have difficulty meeting their fixed financial obligations, the benchmark for income evaluations turns inward. "Financial hardship", the shortfall from one's own previous peak income, takes over, and the greater the shortfall, the less one's happiness. There is thus an asymmetry in the psychological roots of income evaluations when income is rising vs. falling , and this causes a corresponding asymmetry in the response of happiness to the direction of income change.
Keywords: I31; D60; O10; O05; 330; happiness; life satisfaction; subjective well-being; economic growth; GDP; income; easterlin paradox; recession; social comparison; financial hardship